Board secretary and market information efficiency: Evidence from corporate site visits - Weihang Xu; Huijuan Cao; Shuai Qin; Xiangting Kong (China Journal of Accounting Research, 2021)
Using the setting of corporate site visits, this study examines the information interpretation role of board secretaries on market information efficiency. We find that the presence of the board secretary during corporate site visits can significantly improve the information content of such visits. From the perspective of information interpretation ability, when the board secretary has a dual role, receives high relative compensation, and has a high level of education, his or her participation in site visits has a greater effect on improving the informativeness of such visits. From the perspective of information asymmetry, the information interpretation role of the board secretary is more pronounced when the level of information asymmetry between the firm and its investors is high. Further analysis shows that when the board secretary attends more site visits, the level of analyst forecast error is lower. In summary, we confirm the information interpretation role of board secretaries, which is useful for opening the "black box" of their participation in the information assimilation process and for better understanding of how to improve market information efficiency.
Keywords: 650; Board secretary; Information content; Information assimilation; Site visits